Fixed point theorem in a partial b-metric space applied to quantum operations - Tiwari, Rakesh; Khan, Mohammad Saeed; Rani, Shoba; Fabiano, Nicola (Vojnotehnički glasnik / Military Technical Courier, 2022)
Introduction/purpose: A fixed point theorem of an order-preserving mapping on a complete partial b-metric space satisfying a contractive condition is constructed. Methods: Extension of the results of Batsari et al. Results: The fidelity of quantum states is used to construct the existence of a fixed quantum state. Conclusions: The fixed quantum state is associated to an order-preserving quantum operation.